A two-photon fluorescent turn-on probe for nitroxyl (HNO) and its bioimaging application in living tissues. Issue 26 (27th February 2015) - Zheng, Kaibo; Lin, Weiying; Cheng, Dan; Chen, Hua; Liu, Yong; Liu, Keyin
Abstract : The first two-photon fluorescent probe for specific detection of nitroxyl is designed and synthesized, and we have further demonstrated that the new two-photon fluorescent probe could be employed to image nitroxyl in living cells and tissues. Abstract : The first two-photon fluorescent probe for specific detection of nitroxyl is designed and synthesized, and we have further demonstrated that the new two-photon fluorescent probe could be employed to image nitroxyl in living cells and tissues.